2015
DOI: 10.1186/s12864-015-1597-y
|View full text |Cite
|
Sign up to set email alerts
|

Prediction accuracies for growth and wood attributes of interior spruce in space using genotyping-by-sequencing

Abstract: BackgroundGenomic selection (GS) in forestry can substantially reduce the length of breeding cycle and increase gain per unit time through early selection and greater selection intensity, particularly for traits of low heritability and late expression. Affordable next-generation sequencing technologies made it possible to genotype large numbers of trees at a reasonable cost.ResultsGenotyping-by-sequencing was used to genotype 1,126 Interior spruce trees representing 25 open-pollinated families planted over thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
95
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 61 publications
(81 reference statements)
13
95
3
Order By: Relevance
“…Our results revealed that the prediction accuracy estimated in the candidate population (on average r(Â can , Ŷ can ) = 0.242 and r(Ĝ can , Ŷ can ) = 0.242) remained low compared with the goodness-of-fit (on average r(Â full , Ŷ full ) = 0.513 and r(Ĝ full , Ŷ full ) = 0.649) and prediction stability (on average r(Â can , Â full ) = 0.747 and r(Ĝ can , Ĝ full ) = 0.567) using the full data set. Although comparisons with other studies should be carried out with caution because the prediction accuracies are calculated according to different methods and formulas, the prediction stability values assessed in our study were similar to those estimated in previous forest tree studies for growth traits (Resende et al, 2012;Muñoz et al, 2014;Beaulieu et al, 2014a, b;Gamal El-Dien et al, 2015). The prediction accuracy defined in our study by r(Â can , Ŷ can ) and r(Ĝ can , Ŷ can ) is supposed to give a more objective genomic selection potential.…”
Section: Impact Of Modeling On the Prediction Accuracysupporting
confidence: 86%
“…Our results revealed that the prediction accuracy estimated in the candidate population (on average r(Â can , Ŷ can ) = 0.242 and r(Ĝ can , Ŷ can ) = 0.242) remained low compared with the goodness-of-fit (on average r(Â full , Ŷ full ) = 0.513 and r(Ĝ full , Ŷ full ) = 0.649) and prediction stability (on average r(Â can , Â full ) = 0.747 and r(Ĝ can , Ĝ full ) = 0.567) using the full data set. Although comparisons with other studies should be carried out with caution because the prediction accuracies are calculated according to different methods and formulas, the prediction stability values assessed in our study were similar to those estimated in previous forest tree studies for growth traits (Resende et al, 2012;Muñoz et al, 2014;Beaulieu et al, 2014a, b;Gamal El-Dien et al, 2015). The prediction accuracy defined in our study by r(Â can , Ŷ can ) and r(Ĝ can , Ŷ can ) is supposed to give a more objective genomic selection potential.…”
Section: Impact Of Modeling On the Prediction Accuracysupporting
confidence: 86%
“…While similar results have been reported for animals [18,43] and crop species [9,36] across a number of traits, in forest trees prediction accuracies using genomic data have generally been similar or up to 10-30% lower than accuracies obtained using pedigree-estimated breeding values, including Eucalyptus [4], loblolly pine (Pinus taeda) [44], white spruce (Picea glauca) [45,46], interior spruce (Picea engelmannii × glauca) [47,48] and maritime pine (Pinus pinaster) [49]. Genomic predictions with lower accuracies than pedigree-based predictions could arise from insufficient marker density, such that not all casual variants are captured in the genomic estimate [41], or an overestimate of the pedigree-based prediction due to its inability of ascertaining the true genetic relationships in half-sib families [47]. Our result however differ from previous studies in forest trees due to the fact that the average pairwise estimates of genetic relationship among individuals were substantially lower using SNP data than expectations based on pedigree information (Table 1), clearly suggesting that the expected pedigrees, and consequently the pairwise relationships, had considerable inconsistencies that were corrected by the SNP data.…”
Section: Genomic Data Corrected Pedigree Inconsistenciessupporting
confidence: 71%
“…Given the relatively long-range LD and relatedness in our populations, our estimates of genomic heritability should closely reflect the amount of additive genetic variance for the traits measured. Genomic heritabilities lower than the pedigree-based estimates were also reported in open-pollinated families of spruce [19, 21]. Pedigree-based heritability estimates from open-pollinated families could be inflated due to the presence of full-sibs or selfs and the inability of these estimates to disentangle the non-additive from the additive genetic components [48].…”
Section: Discussionmentioning
confidence: 99%